Treatment preferences for depression in the elderly - Luck-Sikorski, Claudia; Weyerer, Siegfried (International psychogeriatrics, 2016)
Background: If patients are treated according to their personal preferences, depression treatment success is higher. It is not known which treatment options for late-life depression are preferred by patients aged 75 years and over and whether there are determinants of these preferences. Methods: The data were derived from the German “Late-life depression in primary care: needs, health care utilization, and costs (AgeMooDe)” study. Patients aged 75+ years (N = 1,230) were recruited from primary care practices. Depressive symptoms were determined using the Geriatric Depression Scale (GDS-15). Support for eight treatment options was determined. Results: Medication, psychotherapy, talking to friends and family, and exercise were the preferred treatment options. Having a GDS score ≥ 6 significantly lowered the endorsement of some treatment options. For each treatment option, the probability of choosing the indecisive category “I do not know” was significantly increased in participants with moderate depressive symptoms. Conclusions: Depressive symptoms influence the preference for certain treatment options and also increase indecision in patients. The high preference for psychotherapy suggests a much higher demand for late-life psychotherapy in the future. Healthcare systems should begin to prepare to meet this anticipated need. Future studies should include previous experience with treatment methods as a confounding variable.
Gesehen am 12.04.2018